Cross-national differences in the prevalence and correlates of burden among older family caregivers in the WHO World Mental Health (WMH) Surveys - Shahly, V. (2012)
BACKGROUND: Current trends in population aging affect both recipients and providers of informal family caregiving, as the pool of family caregivers is shrinking while demand is increasing. Epidemiologic research has not yet examined the implications of these trends for burdens experienced by aging family caregivers. METHODS: Cross-sectional community surveys in 20 countries asked 13,892 respondents ages 50+ about the objective (time, financial) and subjective (distress, embarrassment) burdens they experience in providing care to first-degree relatives with 12 broadly-defined serious physical and mental conditions. Differential burden was examined by country income category, kinship status, and type of condition. RESULTS: Among the 26.9-42.5% respondents in high, upper-middle, and low/lower-middle income countries reporting serious relative health conditions, 35.7-42.5% reported burden. Of those, 25.2-29.0% spent time and 13.5-19.4% money, while 24.4-30.6% felt distress and 6.4-21.7% embarrassment. Mean caregiving hours/week given any was 16.6-23.6 (169.9-205.8 hours/week/100 people ages 50+). Burden in low/lower-middle income countries was 2-3-fold higher than in higher income countries, with financial burden given any averaging 14.3% of median family income in high, 17.7% in upper-middle, and 39.8% in low/lower-middle income countries. Higher burden was reported by women than men and for conditions of spouses and children than parents or siblings. CONCLUSIONS: Uncompensated family caregiving is an important societal asset that offsets rising formal healthcare costs. However, the substantial burdens experienced by aging caregivers across multiple family health conditions and geographic regions threaten the continued integrity of their caregiving capacity. Initiatives supporting older family caregivers are consequently needed, especially in low/lower-middle income countries.